The Use of Acoustic Doppler Current Profiler (ADCP) to Determine the Water Velocity as Related to Sediment Deposition in Epe Lagoon, Lagos State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
Sediment deposition poses significant challenges to marine transport, aquatic ecosystems, and hydrogeological exploration. This study investigates the integration of Acoustic Doppler Current Profiler (ADCP) data with grain size analysis to estimate sediment deposition velocities in a lagoonal environment. Data from ten ADCP measurements revealed varying velocities, with the highest at 7.70 ft/s and the lowest at 0.99 ft/s. Analysis of ADCP data indicated high velocity zones at depths of 21 to 27 ft and 12 to 19 ft, while low velocities were observed at shallow depths (up to 18 ft) and near the bottom at specific locations. Concurrent grain size analysis identified a predominance of coarse-grained sand, with varying degrees of sorting from moderately well to poorly sorted sediments. The results demonstrated that areas of high sediment velocity are associated with larger grain sizes, whereas low velocity zones correspond to finer grains. This study suggests optimal navigation routes for vessels around the lagoon’s middle and recommends dredging edges to mitigate sediment accumulation. These insights provide valuable guidance for sediment management, coastal engineering, and marine transportation safety.